Functioning in Women with Cervical Cancer in Brazil: the Perspective of Experts - Castaneda, Luciana; Bergmann, Anke; Castro, Shamyr; Koifman, Rosalina (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective The objective of this study was to identify the perspective of the specialists about functioning in women with cervical cancer (CC).Methods A study was conducted with specialists using the Delphi methodology. The specialist contacts were found in oncology organizations and associations, as well as in a referral hospital in the treatment of CC. The questions that the experts answered covered the biopsychosocial domains of the International Classification of Functioning, Disability and Health (ICF).Results Twenty-five specialists participated in the study. The experts' responses generated 485 significant concepts. The categories that presented the highest frequencies of reporting by the specialists were health services, systems and policies; structure of the reproductive system; health professionals and sexual function.Conclusion Regarding the perception of the specialists, this study concluded that 24 categories of ICF are the most relevant in the context of functioning in women with CC. The results suggest that the biopsychosocial perspective was incorporated in the experts' perceptions about the functioning phenomenon in women with CC in Brazil.
Keywords: health personnel; international classification of functioning; disability and health; medical oncology; uterine cervical neoplasms